The Art of Leadership: Analysing Rhetorics in the Linguistic Strategies of the 2020 US Presidential Election - Ridhatul Fadhli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
With a major focus on the rhetorical techniques used by candidates Joe Biden and Donald Trump, this study explores the nuanced linguistic discourse of the 2020 US presidential election. The study, grounded on Aristotle's theory of rhetoric, examines how these linguistic strategies were used in the speakers' speeches to understand how they influenced public opinion and shaped political discourse. The study uses a descriptive-qualitative methodology to arrange and summarise the verbal responses of the applicants systematically, enabling the discovery of recurrent themes and patterns. The results of this study highlight significant differences between the two candidates' rhetorical strategies. Joe Biden expertly combines all three rhetorical appeals—ethos, pathos, and logos—into his communication strategy, unlike Donald Trump, who primarily uses pathos to elicit strong emotional reactions from his audience. This study emphasises the crucial roles of ethical credibility, emotional appeal, and logical argumentation in political communication, underlining their tremendous influence on forming public perception in democracies. This study illuminates the complex dynamics of language use in shaping and affecting public attitudes and views. Beyond its theoretical contributions, this research offers practical insights for linguistics, political science, media studies, and communication studies, elucidating the intricate dynamics of language utilisation in moulding and influencing societal attitudes and beliefs.